Fraud Prevention Legal Certainty Principle In Health Sector and Implementation of Health Insurance Program in Indonesia - Endah Labati Silapurna (Lambung Mangkurat, 2022)
The Corruption Eradication Committee (KPK) says that high number of potential irregularities occurs most often in the health sector and in the implementation of the National health insurance program as obtained through efforts to prevent, coordinate, and synergize with relevant government agencies, such as the BPK, the BPKP, etc. It is important for early detection of fraud along with repressive actions and sanctions that need to be followed up if there is such a potential. The issues to be discussed here are How do the laws and regulations regulate fraud prevention in the health sector in Indonesia, What is the relationship between the statutory norms regarding Fraud Prevention and the Principle of Legal Certainty? This research method uses a normative juridical approach, and the specifications of the data used in this study are qualitative secondary data. The data collection method used is literature study. The conclusion, in the form of a provisional answer: if regulations are formed relating to fraud prevention in Indonesia referring to the 1945 Constitution of the Republic of Indonesia, where everyone is entitled and guaranteed by the constitution to maintain life and receive services maximally, then the principle of legal certainty is fulfilled.